Intravenous Recombinant Tissue-Type Plasminogen Activator Thrombolysis for Acute Central Retinal Artery Occlusion. Issue 1 (January 2021) - Wang, Xiaotang; Liu, Yong; Suo, Yan; Qin, Dan; Ren, Meixia; Lei, Runjia; Zhang, Yanchun; Wang, Ying
Abstract : Introduction: Central retinal artery occlusion (CRAO), an ocular stroke, causes severe and permanent visual impairment. Thrombolytic therapy is currently the main treatment option for CRAO. Intravenous thrombolysis with recombinant tissue-type plasminogen activator (rt-PA) has been extensively applied in the treatment of CRAO with the proven advantages of effectiveness and safety. This meta-analysis aimed to assess the efficacy of intravenous rt-PA thrombolysis for the management of CRAO by evaluating the pooled evidence. Methods: A comprehensive literature search of electronic databases including PubMed, OVID, and Cochrane Library was conducted up to and including March 2019. All studies reporting visual outcomes after CRAO with thrombolytic therapy were collected. Data on visual acuity and adverse events were recorded and assessed in this analysis. Data were inputted into the statistical software of STATA. The studies were weighed by the inverse of the variance and merged in a random-effects model. Results: The systematic review process yielded 7 eligible studies including 121 patients with CRAO who received the intravenous rt-PA treatment. Sixty-two patients showed improvement in visual acuity (52.0%; 95% CI, 34.0%–70.0%) following rt-PA intravenous thrombolytic therapy. The observed improvement rate in the intravenous rt-PA treatment group was significantly higher than the conservative treatment group (40.4% vs. 13.0%; OR = 5.16; 95% CI, 1.90–14.05). The incidence rate of complications was relatively low (11 out of the 121 patients). Hemorrhage (9/11) was the major reported complication. Mortality was zero. Discussion: This meta-analysis indicated that intravenous rt-PA thrombolysis could be an effective and safe strategy for the management of CRAO. However, a more detailed large-scale clinical trial is warranted to strengthen the evidence-based therapeutic guidance. Abstract : Supplemental Digital Content is available in the text